Johnson's Practical Electromyography Fourth edition - William S. Pease (2007)
In the years since the release of the third edition of Johnson's Practical Electromyography, the science of electrodiagnostic medicine has advanced greatly. As our understanding leads us to use different, new, or redefined words it becomes necessary to replace the old edition. New organizations and Board certification exams, and new names for old organizations demonstrate the vitality of this special area of medicine. More than just a set of tests, electromyography in practice is the specialized use of these tools for the evaluation and treatment of persons with nerve and muscle pathology. The electrodiagnostic medicine consultant plays valuable roles in the diagnosis and the treatment of disorders of function of the nervous system. The physician is then able to translate this knowledge into improving the motion and function of the body. A particularly valuable addition to this edition began with a chance encounter on the beach at Hilton Head during a meeting of the Association of Academic Physiatrists. Henry Lew began discussing a special process that he was using to create digital images to improve learning of the basic techniques of nerve conduction based upon surface anatomy. The collaborative process with Bill and Ernie was accomplished by reviewing hard copies in person, and making revisions via email exchanges. We are proud to now share the results with you. We are pleased that the new edition recognizes Ernie Johnson for his invaluable contributions to the field of electromyography. His continuing observations and insights are seen in his chapters in the text, and his always-challenging test in the appendix. You may also challenge yourself online and earn CME credit for your efforts. We are pleased to include recorded EMG video clips to further stimulate your learning; remember to have the audio on with the videos as the sounds of many EMG signals is unique and distinctive. The book includes contributions from an international group known for their intelligence, teaching ability, and commitment to this specialty. We are grateful for their participation in this effort, and more so for their continuing friendships.